2016
DOI: 10.1016/j.scog.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in patients at ultra-high risk for psychosis: What is the relation to social skills and functioning?

Abstract: ObjectivePatients at ultra-high risk (UHR) for psychosis show significant impairments in functioning. It is essential to determine which factors influence functioning, as it may have implications for intervention strategies. This study examined whether social cognitive abilities and clinical symptoms are associated with functioning and social skills.MethodsThe study included 65 UHR patients and 30 healthy controls. Social cognitive function, social skills, and a broad range of functioning measures were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 53 publications
(66 reference statements)
4
47
1
Order By: Relevance
“…Current approaches did not produce significantly larger effects on social functioning than control conditions Van der Gaag et al, 2013). Thus, novel interventions are needed to directly target factors modulating social functioning, such as social cognition (Cotter et al, 2017;Glenthøj et al, 2016;Schmidt, Mueller, & Roder, 2011).…”
Section: Need For Integrated Preventive Psychological Interventionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Current approaches did not produce significantly larger effects on social functioning than control conditions Van der Gaag et al, 2013). Thus, novel interventions are needed to directly target factors modulating social functioning, such as social cognition (Cotter et al, 2017;Glenthøj et al, 2016;Schmidt, Mueller, & Roder, 2011).…”
Section: Need For Integrated Preventive Psychological Interventionsmentioning
confidence: 92%
“…Current approaches did not produce significantly larger effects on social functioning than control conditions (Schmidt et al, ; Van der Gaag et al, ). Thus, novel interventions are needed to directly target factors modulating social functioning, such as social cognition (Cotter et al, ; Glenthøj et al, ; Schmidt, Mueller, & Roder, ). Social cognition as the mental operations underlying social interactions comprises the following domains: social and emotional perception, Theory of Mind and social attribution styles (Green et al, ; Pinkham, Penn, Green, & Harvey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Speci c to the relationship between TASIT and SRS, a prior study did not nd a signi cant association between TASIT performance and SRS in 22q11DS (48) in line with our ndings. One study on adult CHR participants found a signi cant association between higher TASIT scores and lower self-reported SRS scores (50). Another study on adults ASD participants found a signi cant association between higher TASIT scores and higher self-reported SRS scores (86).…”
Section: Discussionmentioning
confidence: 99%
“…The original SRS administered to parents/caregivers of the FEP group was rescored using the updated norms for the revised version (SRS-2), both of which have the same items, so as to be consistent across all groups. The SRS was originally developed to quantify (dimensionally measured) social impairments within the context of the ASD phenotype, but has now been extended to many other clinical populations, including 22q11DS (20,48), CHR (21,49,50), and FEP (21,49). It has also been shown to index traits that are continuously distributed in the general population (51).…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…• Range: 1-5 • Higher scores indicate poorer functioning • Global measure derived from 3 to 6 role area scores: Occupational performance, social and leisure functioning, and physical well-being, relationship with family/marital/ children, domestic life, and financial situation 1.59 AE 0.33 (Weissman et al, 1978) CBT: 3.7 AE 0.85; SC: 3.5 AE 1.0 (Bechdolf et al, 2007) Social functioning scale (SFS) • Normalized to mean = 100 SD = 15 • Lower scores indicate poorer functioning • Global measure derived from 7 sub-scores: withdrawal/social engagement, interpersonal communication, independence-performance, independence competence, recreation, prosocial and employment/occupation 161.65 AE 20.23 125.29 AE 22.77 Social and occupational functioning assessments scale (SOFAS) (Glenthøj et al, 2016) 56.25 AE 10.02 (Glenthøj et al, 2016) Abbreviations: CBT, cognitive behavioural therapy; SC, supportive counselling.…”
Section: Other Interventionsmentioning
confidence: 99%